Fault-Tolerant Control of Gas-Lifted Oil Well - Ojonugwa Adukwu; Darci Odloak; Fuad Kassab Junior (IEEE Access)
The gas-lifted system has inherent ability to hide the effect of fault hence the system can inject gas into the annulus and oil will still be produced even in the presence of fault of significant value. This however affects the optimal operation of the system and could move the system towards the undesirable casing-heading instability. Faults of step decrease in the valves coefficients in addition to limitation on the valve affect the optimal flow of the liquids through the system. We detect and isolate these faults using generalised likelihood ratio test (GLRT) and Dedicated observer scheme (DOS) respectively. The states of the system are estimated using extended Kalman filter (EKF). Model predictive control based fault-tolerant control is then implemented on the system by using the robustness property of the zone control MPC and limiting the input bound in the optimiser. Both passive and active fault-tolerant control (FTC) were used to improve oil production or stabilise the system. Passive fault-tolerant control (FTC) provides more robustness but it does not change oil production noticeably enough. Reducing the upper control bound ensures stability but production could decline. Increasing the controller cost that prioritises the input target increases production but it is prone to casing-heading instability.